Utility of Awake craniotomy tumor resection in patient with history of long-standing goiter. - Maryam Bashir; Faraz Shafiq (Journal of the Pakistan Medical Association, 2025)
Dear Editor, This letter explores the considerations involved in performing an Awake craniotomy (AC) on a patient with a history of long-standing goiter, highlighting the utility of AC after careful patient selection, multidisciplinary collaboration, and prevention of potential complications. AC is a specialized surgical procedure that allows resection of brain tumors while patient remains conscious. It facilitates in intraoperative neurological monitoring of motor, sensory and speech functions. The potential benefits are maximizing tumor resection, minimizing post-operative neurological defects and better recovery profile 2. However, potential complications require careful consideration and anticipation. Amongst them, airway related events are at the top and, commonly associated with failure of technique and conversion to general anaesthesia3. Our patient was elderly female with history of Diabetes, Hypertension, and Hypothyroidism. She presented with a frontal lobe space occupying lesion. Physical examination revealed, swelling in front of neck because of large goiter predominantly on the left side, but showed no signs of respiratory distress. A thorough examination, including Pemberton's sign, was negative for thoracic inlet obstruction. Chest X-ray confirmed the presence of a large thyroid gland. ENT consultation was done revealed no airway involvement a part from having tracheal deviation. There was no airway obstruction and patient were able to lie supine without any signs & symptoms of respiratory distress. We opted for awake throughout approach. A regional scalp block was performed for perioperative analgesia. To mitigate the associated risks, surgical position was modified so that patient remained. comfortable in terms of breathing. Supplemental oxygen was also given via nasal prong. Close communication was maintained throughout the procedure and conscious sedation was maintained with low dose of Dexmedetomidine infusion (0.1-0.2mcg/Kg/hr.). Procedure was done successfully and patient was shifted to recovery unit. In conclusion, AC presents unique challenges in patients with history of goiter and neck swelling. Through careful patient selection, preoperative evaluation, and a multidisciplinary approach, it is possible to achieve successful outcomes while minimizing risks associated with general anaesthesia.